Review : Potensi Kesehatan Cuka Buah sebagai Pengembangan Obat Tradisional - Permadi, Adi (Institut Teknologi Adhi Tama Surabaya, 2025)
Fruit vinegar is a fermented functional food product with significant health benefits due to its antioxidant-rich composition. Produced through alcoholic and acetic fermentation from starchy or sugary raw materials, fruit vinegar contains bioactive compounds such as organic acids, polyphenols, and melanoidins. These contribute to its roles in blood glucose regulation, weight management, antimicrobial effects, and chronic disease prevention. Variants like apple cider vinegar, pineapple vinegar, and mango vinegar have shown potential as therapeutic agents for diabetes, cardiovascular health, and obesity. Despite its promising applications in modern medicine and food preservation, challenges remain, including limited clinical data, inconsistent product quality, and varying production methods affecting bioactive content. This review explores the health benefits, production processes, and therapeutic potential of fruit vinegar, integrating recent findings to provide insights into its functionality and challenges. Furthermore, opportunities for utilizing alternative substrates, such as mango peels and pineapple waste, highlight its role in promoting sustainability. By addressing current gaps and emphasizing innovation in production and research, this study aims to support the broader application of fruit vinegar in health and food sectors